2018
DOI: 10.1155/2018/8913187
|View full text |Cite
|
Sign up to set email alerts
|

Very Low Volume High-Intensity Interval Exercise Is More Effective in Young Than Old Women

Abstract: We investigated the acute neuromuscular and stress responses to three different high-intensity interval training sessions in young (age 19.5 ± 1.3 years) and older (age 65.7 ± 2.8 years) women. Cycling exercise comprised either 6 × 5 s or 3 × 30 s all-out, or 3 × 60 s submaximal, efforts each performed 5 weeks apart in randomized order. Peak and average power was higher in young than in older women and was largest during the 6 × 5 s strategy in both groups (p < 0.05). The decrease in the ratio of torques evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…There was no main effect of group on brain-derived neurotrophic factor Dropouts: 13 participants withdrew during training (HIIT = 3, MCT = 5, stretching = 5) Compliance: All participants completed at least half of training protocol. Krusnauskas et al (2018) [ 31 ] 3 SIT protocols: 1) 6 intervals of 5 s at “all-out” intensity (90-s rest), 2) 3 intervals of 30 s at “all-out” intensity (4-min rest), or 3) 3 intervals of 60 s at submaximal intensity (4-min rest) Frequency: Single session Modality: Cycle ergometer Decrease in torque ratio represented low-frequency fatigue and was more evident in the 30 s and 60 s protocols. In young women, low volume (6 × 5 s) exercise induces physiological stress and is effective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no main effect of group on brain-derived neurotrophic factor Dropouts: 13 participants withdrew during training (HIIT = 3, MCT = 5, stretching = 5) Compliance: All participants completed at least half of training protocol. Krusnauskas et al (2018) [ 31 ] 3 SIT protocols: 1) 6 intervals of 5 s at “all-out” intensity (90-s rest), 2) 3 intervals of 30 s at “all-out” intensity (4-min rest), or 3) 3 intervals of 60 s at submaximal intensity (4-min rest) Frequency: Single session Modality: Cycle ergometer Decrease in torque ratio represented low-frequency fatigue and was more evident in the 30 s and 60 s protocols. In young women, low volume (6 × 5 s) exercise induces physiological stress and is effective.…”
Section: Resultsmentioning
confidence: 99%
“…Studies considered to be metabolic diseases included populations with type 2 diabetes mellitus (T2DM) [71- Frequency [31] 3 SIT protocols: 1) 6 intervals of 5 s at "all-out" intensity (90-s rest), 2) 3 intervals of 30 s at "all-out" intensity (4min rest), or 3) 3 intervals of 60 s at submaximal intensity (4-min rest) Frequency: Single session Modality: Cycle ergometer Decrease in torque ratio represented lowfrequency fatigue and was more evident in the 30 s and 60 s protocols. In young women, low volume (6 × 5 s) exercise induces physiological stress and is effective.…”
Section: Metabolic Diseasementioning
confidence: 99%
“…With the participant in a seated position, maximal voluntary contraction (MVC) isometric peak torque was measured for the knee extensor muscles on the dominant leg using an isokinetic dynamometer (System 3; Biodex Medical Systems). The procedure was previously described by Krusnauskas et al (2018). Briefly, the participant sat in the dynamometer chair with the knee joint positioned at a 60 • angle (0 • = full knee extension).…”
Section: Measurement Of Torquementioning
confidence: 99%
“…We have observed that the exertion level during SIT sessions differs between young and older people [10,15] and that this difference may result in less exercise-induced stress, which may preclude full-scale adaptations in older people. Other populations may also exhibit considerable differences in exertion level.…”
Section: Introductionmentioning
confidence: 96%